PENGARUH DAU, DAK, PAD, DAN PDRB TERHADAP BELANJA MODAL PEMERINTAH DAERAH KABUPATEN/KOTA DI INDONESIA - Askam Tuasikal (Program Magister Akuntansi Unsyiah, 2008)
The purposes of this research is to know whether general allocation fund (DAU), special allocation fund (DAK) regional own revenue (PAD), and brutto regional domestic product (PDRB) influenced capital expenditure local goverments. The research objects are regencie/municipatily of Indonesia. The used data is secondary data that is from governments recorded in table of general budget calucalation. Linier regression was used to analyzed the data. The study finds that DAU, DAK, PAD, and PDRB influenced capital expenditure simultaneously. The other founding only PDRB not influenced capital expenditure partially. Limitation of this research is that the study did nott explore which expenditure sector that is more consume local finance resources. Based on that, the future researcher need to do sector analyze for studying which expenditure sector that is more consume local finance resources and to increase local revenue. Beside of this, to get the better result, for the researcher that want to study the same theme need to add year of observed, for example 5-10 years. Keywords: General allocation fund, special allocation fund, regional own revenue, brutto regional domestic product, and capital expenditur